Improving cellobiose utilization and fermentation by Saccharomyces cerevisiae strains via metabolic and evolutionary engineering - Lanza, Jennifer; Gombert, Andreas; Bermejo, Pamela (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
Engineered yeast chassis are frequently used for the industrial production of biofuels and chemicals. However, after some initial metabolic engineering steps, further optimization of the microbial host is usually required to achieve high product yields and productivities. In this project, we aim to improve the conversion of cellobiose into ethanol by Saccharomyces cerevisiae. For this purpose, we first metabolically engineered cellobiose transporters and intracellular cellobiases into yeast. Subsequently, the engineered strains were subjected to laboratory evolution, in order to improve their growth rates on cellobiose.